Archaeological Excavations of the Medieval Royal Kincardine Landscape, Aberdeenshire, Scotland. Issue 1 (2nd January 2018) - Malloy, Kevin; Hall, Derek
Abstract : KINCARDINE PARK is among the earliest and largest medieval parks in Scotland. It was royally owned and is believed to have served as a hunting park throughout the 13th and 14th centuries. Nearby are the ruins of Kincardine Castle, considered to be associated with the park, and one of the first Scottish stone-built castles. This paper presents the results of excavations conducted in the park landscape, and at the stone-built Scottish castle. New insights are provided on how medieval Scottish parks were constructed and used, and the cultural significance of these monuments is explored .